ChemInform Abstract: LiBSi2: A Tetrahedral Semiconductor Framework from Boron and Silicon Atoms Bearing Lithium Atoms in the Channels. Issue 38 (30th August 2013) - Zeilinger, Michael; van Wuellen, Leo; Benson, Daryn; Kranak, Verina F.; Konar, Sumit; Faessler, Thomas F.; Haeussermann, Ulrich
Abstract The title compound is obtained from an equimolar mixture of LiB and Si under high pressure/high temperature conditions (10 GPa, 900 °C, 1 h, yield given in g).